Peran Beauty Content Influencer Instagram terhadap Perilaku Pembelian di Jakarta - Lisa Puri Handayani; Wisnu Budi Prasetyo (Pusat Riset dan Inovasi Nasional, 2025)
Influencer marketing has grown rapidly over the past decade and has become an essential strategy for businesses and brands to increase sales, visibility, and brand strength in the digital marketplace. This study aims to analyze the influence of influencer characteristics on follower purchase behavior. The research adopts a quantitative approach involving 135 respondents who follow three beauty content influencer accounts on Instagram. Data analysis was conducted using Structural Equation Modeling – Partial Least Square (SEM-PLS) due to the relatively small sample size. The results of the study indicate that the variables influencer trustworthiness, influencer usefulness, influencer attractiveness, influencer experience, and influencer-follower congruence have a positive effect on purchase behavior. However, the moderating effect of influencer attractiveness was rejected due to a mismatch between the influencer’s attractiveness and the followers’ preferences. In contrast, the moderating effects of influencer trustworthiness, influencer usefulness, and influencer experience were accepted, suggesting that trust, perceived usefulness, and experience play a crucial role in shaping followers’ purchasing behavior. The researcher suggests that future studies use the same variables but include a larger number of influencers and more diverse content types to expand follower reach. This approach will allow for more comprehensive hypothesis testing and produce results that are more representative and generalizable.